Healthy Directions of Physical Exercises And Measures For Their Implementation - Nurullaev Abdurashid Ruzimbaevich; M.A.Ruzimbaev (Research Parks Publishers, 2021)
The article discusses the health-improving direction of physical activity and measures for their implementation, the impact of health-improving factors on the body of health-promoting factors in the process of physical education